115 Engineered T cells directed at tumors with defined allelic loss. (9th November 2020) - Hamburger, Agi; DiAndreth, Breanna; Cui, Jiajia; Daris, Mark; Munguia, Melanie; Deshmukh, Kiran; Mock, Jee-Young; Asuelime, Grace; Lim, Emily; Kreke, Michelle; Tokatlian, Talar; Kamb, Alexander
Abstract : Background: Cell therapy, with all its promise as a powerful solid-tumor modality, is still hampered by the fundamental obstacle of cancer therapy: the acute shortage of truly tumor-specific targets. It is well known that an average tumor contains loss of heterozygosity (LOH) at an astonishing frequency: ~20% genome wide. These losses are irreversible and absolutely distinguish the cancer from normal cells. Methods: We describe a novel approach to cancer immunotherapy that draws on LOH as a large, so far untapped source of cancer targets. To exploit such allelic losses, we focus on polymorphic loci and target the remaining allelic product of a locus that has LOH. We engineer T cells with a modular signal-integration circuit designed to be activated only by tumor cells that have lost expression of one specific allele on their surface. Results: We use the HLA locus which undergoes LOH at a frequency of 13%, and the HLA-A*02 allele specifically, as proof of concept. We present a large body of quantitative in vitro data, along with in vivo data, that support the use of a synthetic signal-integration circuit called Tmod as a cancer therapy. We also describe Tmod's mechanistic properties, including thorough structure/function analysis of its components. Conclusions: LOH is a rich source of new targets, provided a system of sufficient power can be devised to exploit them. Our Tmod signal integration system confers on engineered T cells the capacity to discriminate effectively between normal and tumor cells that contain specific allelic losses. Ethics Approval: The animal study was approved by Explora BioLabs' Ethics Board, protocol number EB17-010-059